Analisis Fear of Failure (FoF) pada Mahasiswa Kedokteran - Vidini Caya, Tazkia; Oktafany, Oktafany; Islami, Suryadi (Medula, 2024)
Fear of failure is a person's response to the failure they experience and anticipation to avoid the bad consequences of that failure. Fear of failure can have both positive and negative impacts. Anyone can experience fear of failure, including medical students as students who are pursuing an education full of challenges and responsibilities. Medical students take a longer period of education and bear greater demands and roles than other students. To determine the level of fear of failure, the researchers used a research instrument in the form of a questionnaire, namely the Performance Failure Appraisal Inventory (PFAI). Universally, medical education educates students with the academic achievements that need to be achieved to obtain a license and guarantee a bright future. Without academic achievement and good achievement, degrees and job opportunities, even continuing education will not be easy to obtain. The level of fear of failure varies based on gender, academic year, Grade Point Average (GPA), interest in medical science, etc. Fear of failure shows a negative relationship with medical student learning achievement. Thus, fear of failure in medical students needs to be a concern for educational institutions in understanding student behavior and shaping the scope of teaching and providing counseling that can help medical students overcome the fear of failure.